WANPRESTASI DALAM PERJANJIAN KREDIT DI LEMBAGA PERKREDITAN DESA (LPD) NUSASARI KABUPATEN JEMBRANA - SANJAYA, I KADEK SELIN (FAKULTAS HUKUM UNIVERSITAS WARMADEWA, 2017)
Basically the agreement is an enent where a promised to a other or where two men have promised in carrying out one thing from the events is emerging a relationship between the two people is that in the call engagement. Establish a financial institutions like LPD Nusasari not easy sometimes there is also constraint that in the face of the wanprestasi. From the background over then some problems that will be discussed the as folllows: (1) Factors whetther that caused the wanprestasi in LPD Nusasari?, (2) How ettorts settlement credit jammmed in LPD Nusasari in a state of wanprestasi?. The research in writing thesis, used the kind of research in impiris is in the perpective juridical intended to explain the legality rules asas law, and the aspects of law. The source of the data, the primary data sources that is a number of information or the fact that so directly obtained at location research, secondary data is in the form of these laws provide an explanation about the primary law, which is used in the form of books, the opinion of the law, the results of scientific from the law. The techniques collecting data, namely the collection of used data is a study of the data obtained directly, on the object research is in a way observations namely observations, collecting data that is the technique of the interview with the way asked responsible indirectly or written by the respondents. Data analysis, engineering data analysis used in the thedescritive reasearch is conducted in kualitatif namely techniques data analysis which aims to demystify and take the truth of the study literature it regulation about the credit, then combined with the opinion of the respondents. Conclusion, the factors that caused the wanprestasi in the credit in LPD. Factors internal the cause of the onset of credit jammed is a deviation in the implementation of the procedure credit,faith less good from the owner, administrators, or employees bank, sickly system in the administration and scrutiny credit and sickly system information credit jammed. External factors is a factor that comes from a happened beyond the reach of the ability of debtor or circumstances force (overmacht) as a state of the economy of the tidal stable and the existence of the recession. Factors external hard controlled, but there’s always a way to minimizeor avoid it, if we alert and enterprising supervise. The reaction quickly withthe right in the need to minimize risks arising. The settlement credit jammed in LPD in a state of wanprestasi namely through the legal a litigation (completion problem outside court ) abitrase, the negotiation, and mediation is the first step often do the LPD in addressing wanprestasi. Key words: the credit, factors cause wanprestasi, as a reasult of the law.